Water Resource Availability Assessment Through Hydrological Simulation Under Climate Change in the Huangshui Watershed of the Qinghai–Tibet Plateau - Fu, Zhenghui; Xie, Yulei; Zhang, Yang; Jiang, Xia; Guo, Huaicheng; Wang, Shuhang (Frontiers in Earth Science, 2022)
The related dynamic change of meteorological and hydrological parameters is critical for available water resources, development management options, and making informed decisions. In this study, in order to enhance the resolution of the predicted meteorological and hydrological parameters under climate change, a general framework from integrating with Statistical Downscaling method (SDSM), Generalized Regression Neural Network (GRNN) model, Soil and Water Assessment Tool (SWAT) model, and the improved Tennant method was advanced for available water resources assessment in Huangshui watershed of Qinghai-Tibet Plateau with the highest average elevation in the world. The statistical downscaling method and GRNN model were respectively proposed to predict meteorological and precipitation parameters that as the input variables for SWAT model to simulate the hydrological data under climate change scenarios. Considering the meteorological conditions and the high sediment content in the basin, the available water resources are evaluated by the improved Tennant method. The meteorological data of the Xining station from the year of 1958 to 2011 were used to analyze the data dynamic change and mutation trend. The results indicated that although the precipitations would have great increase in the wet season from May to September, the flows and available water resources would decrease as carbon emissions increase under different representative concentration pathways (RCP) scenarios due to the temperature with obvious rise trend in summer on the existing basis.